2017
DOI: 10.1111/jth.13780
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding‐related hospital admissions and 30‐day readmissions in patients with non‐valvular atrial fibrillation treated with dabigatran versus warfarin

Abstract: Essentials Bleeding is a common cause of hospital admission and re-admission in oral anticoagulant users. Patients with dabigatran and warfarin were included to assess hospital admission risk. Dabigatran users had a higher risk of 30-day re-admission with bleeding versus warfarin users. Close monitoring following hospital discharge for dabigatran-related bleeding is warranted. SummaryBackground: Reducing 30-day hospital re-admission is a policy priority worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Title and abstract screening excluded 12,019 records, a further 289 were excluded after full text screening. Finally, 22 studies were eligible for inclusion in the systematic review [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34]. Only 20 studies were included in the meta-analyses as two scored <6 on the Newcastle–Ottawa scale.…”
Section: Resultsmentioning
confidence: 99%
“…Title and abstract screening excluded 12,019 records, a further 289 were excluded after full text screening. Finally, 22 studies were eligible for inclusion in the systematic review [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34]. Only 20 studies were included in the meta-analyses as two scored <6 on the Newcastle–Ottawa scale.…”
Section: Resultsmentioning
confidence: 99%
“…While searching for modifiable risk factors for readmission, researchers have focused on specific diagnoses11 and high-risk medications such as anticoagulants 12…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is anticipated that patients taking oral anticoagulants will increase in number significantly. Despite their established efficacy, oral anticoagulants have also been implicated in complications including major gastroenterological and/or intracranial bleeding, with associated need for hospitalisation and readmission 12. Weeda et al compared the outcomes (including readmission) for about 8800 patients admitted to the hospital for pulmonary embolism treated with rivaroxaban and warfarin (bridged with heparin) 17.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that dabigatran, which is commonly preferred by clinics because it is a safe and effective alternative to warfarin and does not require dose adjustment according to coagulation tests, may lead to severe bleeding in many tissues and organs, including intracranial bleeding (23). However, this drug represses proliferation in intervertebral disc tissue cells and disrupts the ECM structure.…”
Section: Figurementioning
confidence: 99%